Mucosal characteristics of pelvic ileal pouches. Issue 1 (January 1991) - de Silva, H J; Millard, P R; Kettlewell, M; Mortensen, N J; Prince, C; Jewell, D P
Abstract : This study aimed to investigate the degree of colonic metaplasia in ileo - anal pouches. Biopsy specimens from 25 patients with functioning pouches, eight of whom had pouchitis, were studied using routine histology, mucosal morphometry, mucin histochemistry, and immunoperoxidase staining with monoclonal antibodies directed towards a 40kD colonic protein and a small bowel specific disaccharidase-sucrase isomaltase. Thirteen patients (including all eight with pouchitis) had subtotal or total villous atrophy and crypt hyperplasia. In this group, nine had colorectal type sulphomucin and the 40kD colonic protein was detected in two. These changes were not observed in patients with less severe villous abnormalities. Sucrase-isomaltase activity was, however, present in all 25 pouch specimens. We conclude that although some ileal pouches acquire certain colonic characteristics, complete colonic metaplasia does not occur.